Computed Tomographic and Histopathological Characteristics of 13 Equine and 10 Feline Oral and Sinonasal Squamous Cell Carcinomas - Strohmayer, Carina; Klang, Andrea; Kneissl, Sibylle (Frontiers in Veterinary Science, 2020)
Squamous cell carcinoma (SCC) is the most common equine sinonasal and feline oral tumour. This study aimed to describe the computed tomographic and histopathological characteristics of equine and feline SCC. Thirteen horses and 10 cats that had been histopathologically diagnosed with oral or sinonasal SCC and had undergone computed tomography (CT) of the head were retrospectively included in the study. CT characteristics of the mass and involved structures were noted. Histological examinations were evaluated according to a human malignancy grading system for oral SCC, which considered four grades of increasing aggressiveness. In horses, the masses were at the levels of the paranasal sinuses (n = 8), mandible (n = 3), tongue (n = 1), and nasal cavity (n = 1). In cats, the masses were at the levels of the maxilla (n = 4), mandible (n = 3), tongue (n = 1), and buccal region (n = 1) and were diffusely distributed (facial and cranial bones; n = 1). Masses in the equine paranasal sinuses showed only mild, solid/laminar, periosteal reactions with variable cortical destruction. However, maxillary lesions in cats showed severe cortical destruction and irregular, amorphous/pumice stone-like, periosteal reactions. CT revealed different SCC phenotypes that were unrelated to the histological grade. For morphologic parameters of the tumour cell population, a variability for the degree of keratinization and number of mitotic cells was noted in horses and cats. Concerning the tumour-host relationship a marked, extensive and deep invasion into the bone in the majority of horses and cats was seen. Most cases in both the horses and cats were categorized as histological grade III (n = 8); four horses and one cat were categorized as grade IV, and one horse and one cat were categorized as grade II. In this study, we examined the diagnostic images and corresponding applied human histopathological grading of SCC to further elucidate the correlations between pathology and oral and sinonasal SCC imaging in horses and cats.